MENINGKATKAN HASIL BELAJAR SISWA TENTANG SERVIS ATAS DALAM PERMAINAN BOLA VOLI MENGGUNAKAN PENDEKATAN PEMBELAJARAN DRIIL DAN BERMAIN PADA SISWA KELAS V SD INPRES LAMAGEWOK - Uban, Yohanes Kopong (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The background in this study is the low value of student learning outcomes which illustrates the low level of ability of 18 grade V students of SDI Lamagewok based on the formative test results of service on volleyball games which are below the ideal value of 5.33. Researchers want to do research in this school by implementing a drift learning approach and playing to improve activities and learning outcomes about top service in volleyball games. The Research Method uses class action. For the population and sample are the fifth grade students of SD Inpres Lamagewok, East Adonara District, East Flores Regency. The research procedures include planning, implementing, observing, and reflecting through the application of driil learning approaches and playing top service activities for fifth grade students of Lamagewok Elementary School Inpres 2016/2017 academic year. Based on the results of discussions with fellow learning colleagues on physical education subjects in class V, the increase in the results of the evaluation at the beginning (Pre Cycle) showed that the average score was very low. After improvement in learning Cycle I and Cycle II experienced a significant increase. The results of the PJOK evaluation for Volleyball games in Class V, where there were 18 students, were obtained as follows: Pre-cycle students who scored 7 and above had 6 people and a class average of 5.33 or 53%, cycle I students who scored 7 and above there are 7 people with a class average of 6 or 60%, cycle II of students who get a score of 7 and above there are 18 people with a class average of 8.22 or 82%. From the data above, there is a significant change in student learning outcomes in each cycle due to learning by using methods and approaches to learning and playing in accordance with the learning material.